A novel Ag/carrageenan–gelatin hybrid hydrogel nanocomposite and its biological applications: Preparation and characterization. (March 2021) - Muthulakshmi, Lakshmanan; Pavithra, U.; Sivaranjani, V.; Balasubramanian, N.; Sakthivel, Kunnathur Murugesan; Pruncu, Catalin Iulian
Abstract: A novel biohybrid hydrogel nanocomposite made of natural polymer carrageenan and gelatin protein were developed. The silver nanoparticles were prepared using the carrageenan polymer as reduction and capping agent. Here, the Ag/Carrageenan was combined with gelatin hydrogel using glutaraldehyde having a cross-link role in order to create the biohybrid hydrogel nanocomposite. The manufactured composite performances were anaylised by UV–visible spectroscopy, Fourier Transform infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), Energy dispersive X-ray (EDX) spectroscopy and Transmission Electron Microscopy (TEM) methods. The swelling behaviour of the Ag/Carrageenan-gelatin hybrid hydrogel nanocomposite was also analyzed. The antibacterial activity was tested against human pathogens viz. S. agalactiae 1661, S. pyogenes 1210 and E. coli . The bacterial cell wall damage of S. agalactiae 1661 was analyzed by scanning electron microscopy. The cytotoxic assay was performed against the A549 lung cancer cells.